Large moths facing steeper decline than small moths in South Korea: Implications for ecosystem dynamics and conservation - Tae-Sung Kwon; Sung-Soo Kim; Dae-Seong Lee; Go Eun Park; Young-Seuk Park (Global Ecology and Conservation, 2024)
Declines in moth abundance and distribution have been reported in various regions, indicating a tendency for large moth species to decrease more strongly than smaller moth species. To investigate whether these trends are evident in South Korea, data on moths surveyed using light traps at 18 forest sites in South Korea in the past (1978–2002) and in the recent (2011–2016) periods were analyzed. Specifically, focusing on large moths, the analysis revealed a clear correlation between moth size and decline in occurrence, with large moths experiencing a more significant decrease. Although light pollution is recognized as a factor affecting moth populations, particularly those with extensive migration patterns, our study yielded unexpected results when areas based on night light intensity were compared. Declines in large moth populations were more pronounced in regions with lower night light intensities, indicating a weak influence of light pollution. Morphological traits, such as wingspan, were found to influence moth distribution, with large moths demonstrating steeper declines, thus affecting ecosystem dynamics. Statistical analyses revealed significant influences of wingspan, family, and food type on the occurrence of moths. Moths from open habitats exhibited a greater decline than those dwelling in forests, whereas species with narrower food niches displayed more substantial reductions. Forest recovery in South Korea has induced changes in moth community composition. These findings underscore the need for systematic monitoring and a comprehensive understanding of ecological dynamics to effectively guide moth population conservation efforts in South Korea.